2017
DOI: 10.1038/srep41288
|View full text |Cite
|
Sign up to set email alerts
|

Endothelia-Targeting Protection by Escin in Decompression Sickness Rats

Abstract: Endothelial dysfunction is involved in the pathogenesis of decompression sickness (DCS) and contributes substantively to subsequent inflammatory responses. Escin, the main active compound in horse chestnut seed extract, is well known for its endothelial protection and anti-inflammatory properties. This study aimed to investigate the potential protection of escin against DCS in rats. Escin was administered orally to adult male rats for 7 d (1.8 mg/kg/day) before a simulated air dive. After decompression, signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Escin, the main active compound of horse chestnuts, 6 has been widely used to treat swelling, exudation, and inflammation. 7 Recently, accumulated experimental evidence has shown that escin is a potential cancer chemotherapeutic and has elucidated some of the underlying mechanisms.…”
mentioning
confidence: 99%
“…Escin, the main active compound of horse chestnuts, 6 has been widely used to treat swelling, exudation, and inflammation. 7 Recently, accumulated experimental evidence has shown that escin is a potential cancer chemotherapeutic and has elucidated some of the underlying mechanisms.…”
mentioning
confidence: 99%
“… 22 23 In addition, the improvement of vascular function was also found to be protective on DCS. 24 Our study revealed that bubbles secondary to decompression could induce the production of microparticles 22 which also induced the polarization of macrophages. 25 In addition, microbubbles in the blood vessels may cause ischemia and subsequent alteration of vascular permeability, leading to the leakage of plasma.…”
Section: E Vidence On the R Ole Of mentioning
confidence: 63%
“…For regular divers, even if decompression protocols are strictly followed during each dive, bubbles may still form in the body, 35 which may protect endothelial cells against future injuries through moderately up-regulating autophagy. As endothelial targeting protection has been shown to prevent DCS, [5][6][7] we speculate that increased tolerance to DCS in regular divers might be, at least in part, related to moderate up-regulation of endothelial autophagy. Related rat-model experiments are currently F I G U R E 7 Effects of two consecutive bubble contact on endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Decompression sickness (DCS) is a medical concern that threatens the safety of divers and is associated with bubbles that may appear during or after decompression, even after strictly following diving protocols . Endothelial dysfunction occurs following decompression in divers, and endothelial protective agents have proven beneficial to DCS in animal models . It is now widely accepted that endothelial injury triggered by bubbles plays an important role in the pathophysiology of DCS .…”
Section: Introductionmentioning
confidence: 99%